3T vs. 7T fMRI: capturing early human memory consolidation after motor task utilizing the observed higher functional specificity of 7T - Kreitz, Silke; Mennecke, Angelika; Konerth, Laura; Rösch, Julie; Nagel, Armin M.; Laun, Frederik B.; Uder, Michael; Dörfler, Arnd; Hess, Andreas (Frontiers in Neuroscience, 2023)
Objective: Functional magnetic resonance imaging (fMRI) visualizes brain structures at increasingly higher resolution and better signal-to-noise ratio (SNR) as field strength increases. Yet, mapping the blood oxygen level dependent (BOLD) response to distinct neuronal processes continues to be challenging. Here, we investigated the characteristics of 7T-fMRI compared to 3T-fMRI in the human brain beyond the effect of increased SNR and verified the benefits of 7T-fMRI in the detection of tiny, highly specific modulations of functional connectivity in the resting state following a motor task. Methods: 18 healthy volunteers underwent two resting state and a stimulus driven measurement using a finger tapping motor task at 3T and 7T, respectively. The SNR for each field strength was adjusted by targeted voxel size variation to minimize the effect of SNR on the field strength specific outcome. Spatial and temporal characteristics of resting state ICA, network graphs and motor task related activated areas were compared. Finally, a graph theoretical approach was used to detect resting state modulation subsequent to a simple motor task. Results: Spatial extensions of resting state ICA and motor task related activated areas were consistent between field strengths, but temporal characteristics varied, indicating that 7T achieved a higher functional specificity of the BOLD response than 3T-fMRI. Following the motor task, only 7T-fMRI enabled the detection of highly specific connectivity modulations representing an ‘offline replay’ of previous motor activation. Modulated connections of the motor cortex were directly linked to brain regions associated with memory consolidation. Conclusion: These findings reveal how memory processing is initiated even after simple motor tasks, and that it begins earlier than previously shown. Thus, the superior capability of 7T-fMRI to detect subtle functional dynamics promises to improve diagnostics and therapeutic assessment of neurological diseases.